Development of Learning Media for Electric Motor Installation using an Android-Based Project Based Learning Model for Class XI TITL Students at SMK Negeri 2 Samarinda - Hutasoit, Robert (Educationist: Journal of Educational and Cultural Studies, 2022)
The purpose of Research Development of Electric Motor Installation Learning Media Using This Android-Based Project Based Learning Model is to produce Electric Motor Installation Learning Media Using a valid and practical Android-based Project Based Learning Model. The type of research used in this research is Research and Development Research and Development (R &D) with 4-D development model (define, design, develop, and disseminate). The subject of this study is Android-based Learning Media with Project Based Learning Model in Electric Motor Installation Learning, respondents of this media trial are students of grade XI TITL and grade XI teachers in Electrical Motor Installation Subjects majoring in TITL at SMK Negeri 2 Samarinda. Research instruments are validation questionnaires and questionnaires of practicality of learning media. The results of the response analysis showed that the average value of each validator was declared valid, then the results of practicality obtained the average practicality value by students with practical categories. And practicality results by teachers of subjects obtained value with a very practical category, thus The Learning Media installation of Electric Motor Using the Android-based Project Based Learning Model is declared valid and practical and worthy to be used as a learning medium.